A Comparison of Clock Synchronization in Wireless Sensor Networks. (5th December 2013) - Youn, Seongwook
Abstract : The recent advances in microelectro devices have led the researchers to an area of developing a large distributed system that consist of small, wireless sensor nodes. These sensor nodes are usually equipped with sensors to perceive the environment. Synchronization is an important component of almost all distributed systems and has been studied by many researchers. There are many solutions for the classical networks, but the traditional synchronization techniques are not suitable for sensor networks because they do not consider the partitioning of the network and message delay. Additionally, limited power, computational capacity, and memory of the sensor nodes make the problem more challenging for wireless sensor networks. This paper examines the clock synchronization issues in wireless sensor networks. Energy efficiency, cost, scalability, lifetime, robustness, and precision are the main problems to be considered in design of a synchronization algorithm. There is no one single system that satisfies all these together. A comparison of different clock synchronization algorithms in wireless sensor networks with a main focus on energy efficiency, scalability, and precision properties of them will be provided here.